Do Schools Discriminate Against Homosexual Parents? Evidence from an Internet Field Experiment - Luis Diaz-Serrano; Enric Meix-Llop (Institute for the Study of Labor (IZA), 2015)
The recognition of homosexual rights is a controversial issue in many countries. Spain was the third country in the world (after Netherlands and Belgium) to introduce a law recognizing homosexual marriage and adoption of children. In this paper, we examine for the first time whether schools are more hesitant to give feedback to homosexual parents during children's pre-registration period in Spain. In order to do that, we designed an internet field experiment to be conducted in schools. We created three types of fictitious couples; one heterosexual, one male homosexual and one female homosexual, and send emails to schools making sexual orientation explicit. Our results show that men homosexual couples had a significant lower probability to receive and answer than heterosexual couples (22.5 percentage points less). No statistically significant differences in the response rate were found between female homosexual and heterosexual couples. This result suggests that male homosexual couples might be penalized because of the lack of a maternal figure.
Keywords: H41; I20; K36; 330; discrimination; field experiment; schools; homosexual rights